The Role of the African Languages Research Institute in Addressing Language of Instruction Dilemmas in Zimbabwe - Masuku, Jesta; Ndhlovu, Finex (Lexikos, 2007)
Abstract: The lexicographic work of the African Languages Research Institute (ALRI) has played a significant role in attempting to avoid some of the dilemmas associated with using African languages as media of instruction in the Zimbabwean education system. Monolingual Shona and Ndebele dictionaries, biomedical reference works, dictionaries of musical, literary and linguistic terms as well as children's dictionaries constitute part of ALRI's contribution towards the goal of mainstreaming African languages in the education system. This article is an evaluation of the research activities taking place at ALRI. The aim of the article is to demonstrate that if they receive adequate attention through corpus planning, African languages possess the capacity to play an important role as media of instruction across the entire spectrum of the education curricula in Zimbabwe and elsewhere. The article concludes by observing that, if the efforts of ALRI are to succeed, there is need for the co-operation of all stakeholders in language practice.Keywords: DICTIONARIES, LEXICOGRAPHY, LEXICOGRAPHER, LEXICOGRAPHIC RESEARCH, INDIGENOUS AFRICAN LANGUAGES, AFRICAN LANGUAGES RESEARCH INSTITUTE (ALRI), EDUCATION, CURRICULUM, MEDIUM OF INSTRUCTION, SHONA, NDEBELE, ZIMBABWEOpsomming: Die rol van die African Languages Research Institute by die hantering van onderrigtaaldilemmas in Zimbabwe. Die leksikografiese werk van die African Languages Research Institute (ALRI) het 'n betekenisvolle rol gespeel om sommige van die dilemmas te probeer vermy wat gepaard gaan met die gebruik van Afrikatale as onderrigmedia in die Zimbabwiese opvoedingstelsel. Eentalige Sjona- en Ndebelewoordeboeke, biomediese naslaanwerke, woordeboeke van musiek-, letterkunde- en taalkundeterme sowel as woordeboeke vir kinders maak deel uit van ALRI se bydrae tot die doelwit om Afrikatale in die hoofstroom van die opvoedingstelsel te plaas. Hierdie artikel is 'n beoordeling van die navorsingsaktiwiteite wat by ALRI plaasvind. Die doel van die artikel is om te toon dat, indien hulle voldoende aandag deur korpusbeplanning ontvang, Afrikatale die vermoë besit om 'n belangrike rol as onderrigmedia oor die hele spektrum van die opvoedingsleerplanne in Zimbabwe en elders te speel. Die artikel sluit met die waarneming dat, indien die pogings van ALRI wil slaag, daar behoefte is aan die same-werking van alle belanghebbendes in die taalpraktyk.Sleutelwoorde: WOORDEBOEKE, LEKSIKOGRAFIE, LEKSIKOGRAAF, LEKSIKO-GRAFIESE NAVORSING, INHEEMSE AFRIKATALE, AFRICAN LANGUAGES RESEARCH INSTITUTE (ALRI), OPVOEDING, LEERPLAN, ONDERRIGMEDIUM, SJONA, NDEBELE, ZIMBABWE